Experimental Periodontitis Deteriorated Atherosclerosis Associated With Trimethylamine N-Oxide Metabolism in Mice - Xiao, Lingling; Huang, Lingyan; Zhou, Xin; Zhao, Dan; Wang, Yan; Min, Haiyan; Song, Shiyu; Sun, Weibin; Gao, Qian; Hu, Qingang; Xie, Sijing (Frontiers in Cellular and Infection Microbiology, 2022)
Background Periodontitis is considered a risk factor for atherosclerosis, but the mechanism is not clear. It was reported that oral administration of Porphyromonas gingivalis altered the gut microbiota in mice. Gut dysbiosis and the intestinal metabolite trimethylamine N-oxide (TMAO) were verified to be associated with atherosclerosis. Therefore, the possible TMAO-related mechanism between periodontitis and atherosclerosis needs to be explored. Methods Experimental periodontitis was established by oral administration of P. gingivalis for 2 months in ApoE−/− mice. Mouse hemi-mandibles were scanned using Micro-CT. Quantification of TMAO was performed using liquid chromatography–tandem mass spectrometry. Mouse feces were collected and the bacterial DNA was extracted, then the gut microbiota was analyzed using 16S rRNA genes. Atherosclerotic lesion areas were quantified. Livers, small intestines, and large intestines were analyzed for gene expression. Results Aggravated atherosclerosis plaques were found in experimental periodontitis mice. Plasma TMAO, a pathogenic factor of atherosclerosis, was initially found to be increased in periodontitis mice. Changes in the composition and abundance of the intestinal microflora of periodontitis mice were found. Flavin monooxygenase 3 (FMO3), the catalyzing enzyme of TMAO in the liver, was significantly increased, accompanied by an increase of IL-6 in liver, the abnormal intestinal integrity and enhanced plasma LPS. The IL-6 and LPS were verified to be able to increase FMO3 in HepG2 cells. Conclusion Our research discovered that experimental periodontitis in ApoE−/− mice induced gut dysbiosis and an increase in TMAO. These results suggest a possible mechanism by which periodontitis may accelerate atherosclerosis by influencing the intestinal microbes and the metabolism, which were triggered by inflammation of the liver and intestine.